KEUNIKAN METODOLOGI TAFSIR AL-FARRA: MA’ANI AL-QUR’AN - Abdul Rohman; Barikli Mubaroka (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Ilmu Al-Qur'an Al Multazam Kuningan, 2024)
The Al-Farra Commentary is the oldest and first commentary in the history of exegesis, and its manuscript has survived to the present day. Its presence has been a source of inspiration for commentators who lived after him. From a content perspective, the commentary has its own uniqueness. The purpose of this writing is to reveal the uniqueness of the Al-Farra exegesis methodology entitled